2022
DOI: 10.3390/jcm11237025
|View full text |Cite
|
Sign up to set email alerts
|

Acromial and Scapular Spine Fractures following Reverse Total Shoulder Arthroplasty—A Systematic Review of Fixation Constructs and Techniques

Abstract: Fractures of the acromion and the scapular spine are established complications of reverse shoulder arthroplasty (RSA), and when they occur, the continuous strain by the deltoid along the bony fragments makes healing difficult. Evidence on treatment specific outcomes is poor, making the definition of a gold standard fixation technique difficult. The purpose of this systematic review is to assess whether any particular fixation construct offers improved clinical and/or radiographic outcomes. A systematic review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
(148 reference statements)
0
6
0
Order By: Relevance
“…Cassidy 3 concluded that double-plating has the highest chance of achieving union and biomechanically strong enough to withstand the extra strain of the acromion-spine of scapular region in setting of RSA confirmed by Katthagen 8 biomechanical study. Among the various possible plate positions (superiorly supraspinatus fossa, spine of scapula-posterior position, and caudally-infraspinatus fossa); they 3 concluded single plate has potential highest strength in posterior position and dual plating when combine posterior and caudal position which was the position of choice in author’s cases.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Cassidy 3 concluded that double-plating has the highest chance of achieving union and biomechanically strong enough to withstand the extra strain of the acromion-spine of scapular region in setting of RSA confirmed by Katthagen 8 biomechanical study. Among the various possible plate positions (superiorly supraspinatus fossa, spine of scapula-posterior position, and caudally-infraspinatus fossa); they 3 concluded single plate has potential highest strength in posterior position and dual plating when combine posterior and caudal position which was the position of choice in author’s cases.…”
Section: Discussionmentioning
confidence: 94%
“…In 2 other studies, Morella 13 and Ascione 1 came to a very similar conclusion (0% of inlay vs. 7.9% of onlay and 4.3% in onlay compared to 1.3% reported literature on Grammont style, respectively). Cassidy 3 did not report the type of implant been used among their pooled data of SSF. Sußiek 17 reported pooled result of 11 studies reporting SSF after RSA; among the 50 cases, 2 did not report the type of implant, 21 used Grammont style RSA (mainly Delta III, Depuy Synthes, Raynham, MA, USA), and 27 lateralized implants (mainly Ascend flex; Tornier, Bloomington, MN, USA following by DJO surgical, Lewisville, TX, USA).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the ideal treatment is unclear, a period of nonoperative immobilization in an abduction sling is common 6 . Fractures amenable to surgical management (Levy types IIb-III) are often single or dual-plated with variable results 24,25 . The optimal management of acromion and SS fractures, including indications for prophylactic plating, is evolving, and limited treatment series are currently available.…”
Section: Classification Systemsmentioning
confidence: 99%